Nilai Sosial dalam Novel Negeri 5 Menara Karya Ahmad Fuadi - Ichsan, Maulana; Nurhanisa, Linda (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya, 2023)
In today’s era, many individual tend to overlook the principles of etiquette. This poses a serious problem as humans inherently cannot live in isolation. Therefore, it is important to maintain relationships by adhering to the principles of social reality. This is crucial for preserving harmony within society. The novel